On Convergence, Ongoing Language Change, and Crosslinguistic Influence in Direct Object Expression in Catalan–Spanish Bilingualism - Silvia Perpiñán (Languages, 2018)
The present study explores two morphological differences in direct object expression between Spanish and Catalan: Differential Object Marking (DOM), and the accusative clitics el /l/ vs. ho /u/. Both phenomena are regulated by semantic features, such as animacy and specificity/definiteness. The study experimentally tested 57 Catalan–Spanish bilinguals with different degrees of language dominance in their comprehension and production of these Catalan constructions in order to explore the degree of structural convergence. The results show that with respect to DOM, bilinguals systematically accept ample optionality, creating a new language variety, the bilingual variety, with properties similar and different from both Spanish and Catalan. With respect to the accusative clitics, a certain degree of functional interference in the grammar of Spanish-dominant bilinguals is found. These results illustrate, on the one hand, structural convergence in DOM, culminating in an internal language change accelerated by language contact, and, on the other hand, incipient language transfer from the dominant language in the expression of accusative clitics.